Modelling Techniques and Family Psychoeducation in Improving Self-Help in Children with Intellectual Disabilities - Ihdalumam, Abdy; Meiyuntariningsih, Tatik (Jurnal Multidisiplin Madani, 2024)
Children with special needs have different characteristics, but they still deserve education and training tailored to their needs. This is especially true for children with intellectual disabilities who struggle to help themselves. Limitations in self-help, which often require support from others around them, require special attention so that they can care for themselves. The purpose of this study is to explain the use of a modelling approach to improve the independence of students with special needs. The technique used is a qualitative approach using a case study that includes clinical observations, interviews, and psychological tests. Based on the evaluation results, ACR was diagnosed with intellectual disability. Self-help is an appropriate intervention option. The intervention consisted of 11 sessions over 10 days using a modelling approach, with baselines of putting on clothes, buttoning clothes, putting on trousers, putting on a belt, and putting on shoes. Findings showed that ACR only failed in one of the five objective behaviours, which was wearing a belt, as ACR still struggled to insert the belt into each hole in the pants